Analisis Kepatuhan Regulasi Perlindungan Konsumen dalam E-Commerce di Indonesia - Sri Lestari Poernomo (LPPM Universitas Ekasakti Padang, 2023)
In Indonesia, e-commerce has experienced significant growth and provides a convenient platform for consumers to shop and transact online. However, the rapid expansion must be balanced with certainty regarding consumer protection. This study aims to analyze e-commerce regulatory compliance from the point of view of business actors and consumers. By examining the challenges faced by businesses and consumer experiences, this study describes the effectiveness of existing regulations and identifies potential for improvement. This study combines qualitative interviews and surveys with a diverse sample of e-commerce merchants and consumers. The research findings show that while regulations exist to protect consumers, their enforcement remains a major challenge. Business actors face complex compliance requirements, causing discrepancies in ensuring consumer safety and trust. On the other hand, consumer awareness of their rights is relatively low, which hinders the use of protective measures. In addition, this research also reveals that the current dispute resolution mechanism needs to be improved to facilitate a speedy and fair resolution. On that basis, it is recommended for the government to simplify existing regulations and educate business actors. A multi-stakeholder approach is also highly recommended to ensure better compliance so consumers can be protected.